Study on Flexural Behavior of Self-Compacting Concrete Beams with Recycled Aggregates - Fang Yu; Min Wang; Dali Yao; Weichuang Yang (Buildings, 2022)
Currently, numerous studies have focused on the differences in the properties of self-compacting concrete with recycled aggregate (RASCC) and normal concrete (NC), while less attention has been paid to the application of RASCC in reinforced concrete structures. In this paper, four-point bending loading tests were performed on seven RASCC beams and four NC beams, considering the parameter of reinforcement ratio, and the flexural properties were analyzed and compared. The results showed that the failure form, moment–deflection curves, and flexural capacity of the RASCC beams were similar to those of the NC beams. However, the cracking moment and the crack width of the RASCC beams were significantly smaller than that of the NC beams. With an increase in the longitudinal reinforcement ratio, the cracking resistance and flexural capacity of the RASCC beams increased significantly. The cracking moment and flexural capacity could be calculated using the method of the Chinese code GB50010-2010. However, compared with the test values, the predicted deflection was slightly less safe, while the maximum crack width calculation was slightly more conservative. Therefore, the current code formula was revised according to the test results.